2021
DOI: 10.5194/mr-2-673-2021
|View full text |Cite
|
Sign up to set email alerts
|

Rapid-scan electron paramagnetic resonance using an EPR-on-a-Chip sensor

Abstract: Abstract. Electron paramagnetic resonance (EPR) spectroscopy is the method of choice to investigate and quantify paramagnetic species in many scientific fields, including materials science and the life sciences. Common EPR spectrometers use electromagnets and microwave (MW) resonators, limiting their application to dedicated lab environments. Here, novel aspects of voltage-controlled oscillator (VCO)-based EPR-on-a-Chip (EPRoC) detectors are discussed, which have recently gained interest in the EPR community. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Considering the different measurement times to acquire a spectrum using the two different instruments (resonator-based EPR: 60 s, EPRoC: 4593 s) it becomes clear that the SNR per second is between 20 and 400 for resonator-based EPR and about 1 for EPRoC, respectively. The sample volume used in the resonator-based EPR spectrometer measurements is about 50 μl, which is about 5 × 10 4 larger than the active volume of the EPRoC 52 (∼1 nl). Therefore, it can be concluded that the EPRoC shows an approximate 100–470 times ( cf.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the different measurement times to acquire a spectrum using the two different instruments (resonator-based EPR: 60 s, EPRoC: 4593 s) it becomes clear that the SNR per second is between 20 and 400 for resonator-based EPR and about 1 for EPRoC, respectively. The sample volume used in the resonator-based EPR spectrometer measurements is about 50 μl, which is about 5 × 10 4 larger than the active volume of the EPRoC 52 (∼1 nl). Therefore, it can be concluded that the EPRoC shows an approximate 100–470 times ( cf.…”
Section: Resultsmentioning
confidence: 99%
“…With the EPRoC both dispersion-like 35,36,45 (frequencymodulated, FM) and absorption-like 46,47 (amplitude-modulated, AM) signals may be detected, while with resonator-based EPR usually only a field-modulated absorption EPR signal is measured. In this work, we only analyse the FM spectra as they benefit from the VCO-array concept, which will be discussed in Section 3 below.…”
Section: Eproc Fm Spectrummentioning
confidence: 99%
“…So far almost all VCO-based EPR experiments presented in the literature have been conducted in the CW mode of operation, the only exceptions being the recent rapid scan experiments presented in [11,17,18]. In order to understand the interaction of the VCO and the electron spin ensemble during and after a pulsed excitation, the steady-state model discussed in the previous section is not sufficient.…”
Section: Pulsed Epr Measurements Using Vcosmentioning
confidence: 99%
“…A promising approach for high sensitivity and low cost ESR spectroscopy on nanoliter and subnanoliter samples is the integration of the sensitivity relevant part of the spectrometer into a single chip having an area of less than 1 mm 2 [6]. Several single chip integrated ESR microsystems have been reported in the last 15 years, with operating frequencies from 8 to 260 GHz and operating temperatures from 1.4 to 300 K. Previously reported single chip integrated ESR microsystem are based on continuous wave (CW) [6][7][8][9][10][11][12][13][14][15], rapid scan [16], and pulsed excitations [17,18]. The reported sensitivity of these sensors are in range from 10 7 to 10 12 spins/Hz 1/2 depending on the operating frequency, temperature, and sensitive volume.…”
Section: Introductionmentioning
confidence: 99%